Quality of Life and Physical Activities of Overweight Adolescents - Suwarsi Suwarsi; Maria Elizabeth (Universitas Respati Yogyakarta, 2023)
Adolescent health and well-being must be at the center of efforts to achieve the Sustainable Development Goals (SDGs) adopted by the World Health Organization in 2030. Another approach is needed by first looking at the quality of life of overweight adolescents and their physical activity behavior to provide suggestions for health interventions for overweight adolescents. This study contributed to test there is a significant difference in the level of involvement in participants' physical activity with the quality of life. Uses a quantitative, cross-sectional design. The sample is 80 overweight adolescents (13-19 years). The data was measured through a questionnaire tested for validity with a value of 0.9. The sample was selected using the snowball method according to the inclusion criteria and data analysis using the Chi-square test. The result of this study is Overall, overweight adolescents are in the low quality of life category 68 adolescents (85%). The most adolescent physical activity in the moderate group was 46 adolescents (57.5%), high physical activity 14 (17.5%), and low physical activity 20 (25.0%). There is no significant difference between the level of physical activity and the quality of life variable for overweight adolescents, p-value (0.3). Recommendations from this study are that various health programs need to be proposed by involving peers through programs increasing adolescents’ abilities and skills in quality of life and adolescents' interest in doing physical activity regularly.